A comparative analysis of anatomical variations of popliteal artery and its branches in concomitant aneurysmal disease. (February 2023) - Troisi, Nicola; Melani, Alberto; Raspanti, Claudio; Panci, Simone; Chisci, Emiliano; Pratesi, Carlo; Michelagnoli, Stefano
Objectives: Open or endovascular treatment of popliteal artery aneurysms (PAAs) is still debated. Data about the popliteal artery anatomy and its branches are essential to plan a surgical approach. The aim of this study was to report the anatomical variations of the popliteal artery and its branches in a population with aneurysmal disease and compare them with a standard population with non-aneurysmal disease. Methods: A retrospective review of consecutive patients who underwent surgical PAA repair in our center between January 2011 and December 2020 was performed. One-hundred-forty-six limbs in 128 patients underwent PAA treatment (Group 1). Computed tomography angiography images using a 128-section configuration were reviewed for anatomical variations of the popliteal artery and its branches. A control population of 178 limbs in 89 patients with non-aneurysmal disease was used to compare the outcomes (Group 2). All limbs were classified according to Kim's classification. The two groups were analyzed and compared by means of nonparametric Pearson chi-square test. Results: Both groups were homogeneous in terms of demographics, risk factors, and clinical presentation. In Group 1, the limbs with PAA were classified as type IA, 133 (91.1%); type IB, 2 (1.4%); type IC, 0; type IIA1, 1 (0.7%); type IIA2, 1 (0.7%); type IIB, 4 (2.7%); type IIC, 0; type IIIA, 3 (2.1%); type IIIB, 0; and type IIIC, 2 (1.4%). In Group 2 the limbs with non-aneurysmal disease were classified as type IA, 163 (91.6%); type IB, 5 (2.8%); type IC, 1 (0.6%); type IIA1, 1 (0.6%); type IIA2, 3 (1.7%); type IIB, 2 (1.1%); type IIC, 0; type IIIA, 3 (1.7%); type IIIB, 0; and type IIIC, 0. No difference in terms of anatomy of the popliteal artery and its branches was found between the two groups ( P = NS). Conclusions: Knowledge of anatomical variations of the popliteal artery and its branches is mandatory in case of the surgical approach. Anatomy in PAA patients is not different. Studies with larger population size are needed to validate these outcomes.